A randomized, placebo-controlled, double-blind study on the effects of SZL on patients with mild to moderate depressive disorder with comparison to fluoxetine. (5th December 2021) - Hu, Yuan; Wang, Yichen; Chen, Chao; Yang, Wenshan; Zhu, Weiyu; Wang, Yuanbo; Liu, Ping
Abstract: Ethnopharmacological relevance: Kaixinsan (KXS) decoction, as an herbal formula, was used to treat the diseases, such as insomnia, amnesia, emotional disorders in ancient china. It has been demonstrated to be active in various animal models resembling human depression with multitarget effects. However, effective verification on the clinical application of KXS is still lacking. Supplements in this knowledge field are urgently needed. Aim of the study: This very first study evaluated the efficacy and tolerability of ShenZhiLing (SZL) tablets (KXS preparation), compared with fluoxetine (FLX, positive comparator), in patients with mild to moderate depressive disorder. Materials and methods: In this randomized, double-blind, parallel-group study, 156 patients with mild to moderate depression without taken any antidepressants in the past 6 months or 4 continuous weeks were randomized to receive either 3.2 g/d SZL plus 20 mg/d FLX placebo (SZL group) or 20 mg/d FLX plus 3.2 g/d SZL placebo (FLX group), for 8 weeks. Their clinical presentations and some metabolic indexes were assessed during the 8 weeks' visiting period. Results: Patients in SZL group showed a statistically significant improvement after 8 weeks of treatment in HAM-D17 score (18.79±2.09 to 4.43±4.71, p<0.001) and self-rating depression scale (SDS) score (58.49±8.89 to 39.84±12.09, p<0.001), but not in N-back total respond time (1145.55±608.26 to 1128.47±387.49, p>0.05). In addition, no significant difference at 8 weeks of treatment was found between SZL and FLX groups in SDS score (39.84±12.09 vs. 36.63±12.44) and N-back respond time (1128.47±387.49 vs. 1089.43±352.08) as well as reduction of HAM-D17 score (14.79±4.88 vs. 15.24±4.29) (p>0.05 for all). However, the serum APOB, APOC3 and ALB levels and LDL-C/HDL-C ratio decreased significantly in patients after SZL treatment, while only APOB/APOA1 ratio decreased significantly in FLX group. Other metabolic indexes did not alter significantly after treated with SZL or FLX. Conclusion: The efficacy and safety profile of SZL are comparable to that of fluoxetine in patients with mild to moderate depression. The beneficial effect of SZL is probably associated with improvement of lipid metabolic balance. Graphical abstract: Image 1